2021
DOI: 10.21037/tp-20-226
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hyperoxygenation in congenital heart disease

Abstract: The importance of prenatal diagnosis and fetal intervention has been increasing as a preventative strategy for improving the morbidity and mortality in congenital heart disease (CHD). The advancements in medical imaging technology have greatly enhanced our understanding of disease progression, assessment, and impact in those with CHD. In particular, there has been a growing focus on improving the morbidity and mortality of fetuses diagnosed with left-sided lesions. The disruption of fetal hemodynamics resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 75 publications
1
16
0
1
Order By: Relevance
“…Altogether, as summarized previously, chronic MH may have beneficial effects on left heart growth (70). In presence of left to right shunting at the atrial level these effects may be limited only to those patients with a somewhat restrictive interatrial communication, but there is no data yet to support this hypothesis.…”
Section: Maternal Hyperoxygenation Therapy To Stimulate Left Heart Gr...mentioning
confidence: 91%
See 1 more Smart Citation
“…Altogether, as summarized previously, chronic MH may have beneficial effects on left heart growth (70). In presence of left to right shunting at the atrial level these effects may be limited only to those patients with a somewhat restrictive interatrial communication, but there is no data yet to support this hypothesis.…”
Section: Maternal Hyperoxygenation Therapy To Stimulate Left Heart Gr...mentioning
confidence: 91%
“…Chronic MH should be initiated at about 50% FiO2 for at least 9 h per day with only few interruptions to avoid repeated changes in fetal hemodynamics (16,70).…”
Section: Maternal Hyperoxygenation Therapy To Stimulate Left Heart Gr...mentioning
confidence: 99%
“…A systematic review of the current literature by Co-Vu et al found that most protocols used 8 L with 100% oxygen by a non-rebreather at a mean gestational age of 33.4 weeks [ 29 ]. The duration of therapy ranges from 10 min in a single session to 3–4 h per day [ 30 ].…”
Section: Maternal Hyperoxia Therapymentioning
confidence: 99%
“…The data presented in this study are openly available in reference number [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
unclassified
“…In patients with HLHS, this manoeuvre can be used to gauge pulmonary vasodilatory capacity, which is significantly reduced in patients with atrial septal restriction and thus can identify patients with abnormal pulmonary vascularity who may prove to be poor candidates for fetal intervention. [38][39][40] In addition, acute maternal hyperoxygenation may facilitate identification of fetuses who may need urgent atrial septostomy after birth. A logical extension would be to determine whether chronic maternal hyperoxygenation could potentially affect left heart growth by increasing flow though the left-side structures.…”
Section: Fetal Diagnosis Of Hlhs and The Role Of Fetal Interventionsmentioning
confidence: 99%